The energy sector in mediterranean and MENA countries - Marcella Nicolini; Simona Porcheri (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper describes the energy sector in the Mediterranean and MENA (Middle East and North Africa) countries. It first analyses the production of energy by fossil and renewable sources and discusses the increasing demand in the area and its consequences. It describes the policy frameworks to promote renewable energy as well as fossil-fuel subsidies, which are still abundant in the MENA area. It presents some avenues for integration across the Mediterranean and finally it discusses the implications of the Arab spring on energy production in the next future.
Keywords: Q42; Q43; Q48; 330; Energy; Mediterranean Countries; MENA Countries; Subsidies